Subject, biopolitic and body: reflextions about care practices in the field of mental health - Gabriela Silvina Bru (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
We have done this paper in the context of a qualitative research. The objective is to explore the subjetivation ́s process in the field of mental health, starting from narratives of diferent social actors and laws in the context of the city of Mar del Plata. In this way it was possible carry out ten interviews with people with chronic mental illness. In the text we are going to try show some subjetivation ́s process in the field of mental health. In the first place, we are going to analyce the topics of our thesis. Then we are going to explain our theory perspective. And finally, we are going to think about the care practices built in the narratives. We think the practices are fundamental because they allow us to watch the subjetivation ́s process in the field of mental health.